Delaying primary closure of classic bladder exstrophy: When is it too late?. Issue 6 (December 2020) - Wu, Wayland J.; Maruf, Mahir; Manyevitch, Roni; Davis, Rachel; Harris, Kelly T.; Patel, Hiten D.; DiCarlo, Heather N.; Gearhart, John P.
Summary: Introduction: With current trends towards delaying the closure of classic bladder exstrophy (CBE), bladder growth rate or ultimate capacity may be impacted. Objective: To examine consecutive bladder capacities in CBE patients who had primary closures at differing ages and determine whether there is an optimal age for closure, with reference to bladder capacity. Study design: A retrospective review was performed using an institutional database. Inclusion criteria: CBE, successful neonatal (i.e. ≤28 days old) or delayed (i.e. >28 days old) primary closure, at least three consecutive bladder capacities or two measures taken 18 months apart, and first bladder capacity measured ≥3 months after closure. Only capacities prior to continence surgery and before 14 years of age were considered. Two cohorts were created: neonatal and delayed closure. To account for repeated measurements per patient, a linear mixed model evaluated effects of age and length of delay on bladder capacity based on closure cohort. Individuals in the delayed closure group were further stratified into quartiles to assess for detriment to the bladder based on length of delay. Results: The cohort included 128 neonatal and 38 delayed patients. Median age at closure for the delayed group was 193 days (IQR 128–299). Based on univariate analysis, for the first three capacity measurements, the delayed group had significantly lower capacities despite having a similar median age when the measurements were taken. Linear mixed effects model showed significantly decreased total bladder capacity in delayed closure compared to neonates. The 2nd and 4th quartile groups had the most significant decreases in capacity. Discussion: Time points for the most significant decline appear after the 2nd and 4th quartiles, representing 4–6 months and beyond 9 months, respectively. From this, the authors theorize that the appropriate time to close an exstrophy patient is as early as possible (1st quartile), or, if a delay is needed for growth of a bladder template, then between 6 and 9 months (3rd quartile). There may be a detriment to growth rate, however, statistical power may be lacking to discern this. Study limitations include the single-centered, retrospective design. However, results described here fill an important deficit in the knowledge of managing CBE. Conclusions: All patients in the delayed bladder closure group demonstrated a decline in bladder capacity compared to the control neonatal closure group, with significant differences in the 2nd and 4th quartiles. Thus, closing the bladder prior to nine months of age is recommended. Summary Figure Linear mixed effects model with random intercepts. Each line represents the predicted bladder capacity for a given age. Model without (top) and with (bottom) interaction. The equation for each line is depicted with the corresponding groups denoted by the subscript. Bcap = Bladder Capacity, n = neonatal closure, subscript numbers = quartile group for delayed closure. Summary Figure 1